Mechanical Behavior and Response Characteristics of Overlying Strata in Remining Longwall Top‐Coal Caving Working Face - Defu Zhu; Zhanguo Cheng; Huibo Xia; Yujiang Zhang (Energy Science & Engineering)
ABSTRACT In the remining working face of thick coal seams, the instability of coal pillars near abandoned roadways can lead to advance fractures in the main roof, posing a significant threat to production safety. This study classifies roof collapse characteristics into four types and analyses the pillar instability mechanism using the Bieniawski formula and load estimation methods. A structural mechanics model is developed to predict the fracture location of the main roof based on bending moment distribution, influenced by factors such as pillar width, static load, cantilever length of the goaf, stress concentration, and abandoned roadway width. The fracture line is determined by the location of the maximum bending moment, and a mechanical model is developed to compute the hydraulic supports' working resistance. Theoretical calculations for three coal mines—Shiku, Hanzui, and Shenghua—yield maximum support resistances of 8757.25, 7810.09, and 10,034.46 kN, respectively, aligning well with measured mine pressure data. Results indicate that increased cantilever length and roadway width reduce pillar stability, shifting the maximum bending moment farther from the coal wall. This study provides a basis for selecting hydraulic supports and ensuring safe remining operations, offering theoretical guidance for addressing roof fractures and mine pressure management.